Optimalisasi Penggunaan Aplikasi Venus Dalam Verifikasi Dokumen Awak Kapal di PT Pertamina International Shipping - Abel Audina; Sitti Syamsiah; Muhammad Hidayat (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study aimed to analyze the optimization of the VENUS Application and its impact on time efficiency, cost efficiency, and the effectiveness of administrative processes The research was conducted at PT Pertamina International Shipping during the researcher’s shore-based internship (PRADA) from July 2024 to July 2025. A descriptive qualitative method was employed, using primary data collected through observation, interviews, and documentation. Data were analyzed using an interactive model consisting of data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of the VENUS Application has been effective and optimal. The application has improved time efficiency, reduced administrative and transportation costs, and enhanced the effectiveness of the document verification process. In addition, it facilitates digital document management and monitoring. Nevertheless, further user training, system socialization, and stronger internet network support are required to maximize the application’s effectiveness.